Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae) - Marshall, Stephen A. (Zootaxa, 2020)
The genus Systellapha Enderlein, currently treated as part of Grallipeza Rondani, is resurrected and redescribed to include S. ornatithorax Enderlein and two new species, S. digifurca and S. ornatifemur. The genus is diagnosed by its extremely broad palpus and characteristic silvery thoracic vittae, and further defined by characters of the male and female terminalia.